The Development of Computational Biology in Pakistan: Still a Long Way to Go - Ilyas, Muhammad; Sadique, Samrene; Masood, Kahlid; Qamar, Raheel; Chohan, Shahid Nadeem (PLoS computational biology, 2011)
[...]institutions have now increased to 14. Since the introduction of the field in Pakistan many workshops and conferences have also been organized by public and private institutions. Including Bioinformatics in the Biology Curriculum Because of the importance of bioinformatics to the biological sciences, in 2006 the Higher Education Commission of Pakistan (HEC) defined a curriculum for a BS bioinformatics degree program and advised all public and private universities to include bioinformatics as a subject in the curriculum of all undergraduate biology degree programs(http://www.hec.gov.pk/InsideHEC/Divisions/AECA/CurriculumRevision/Documents/Bioinformatics-2006.pdf).\n Their research aims include (http://imsb.edu.pk/home.htm) mechanisms of multifunctional behavior of proteins, transitory proteins, transcription factors, transitory genes, and modification of proteins and glycoproteins; modification potential of proteins relevant to phosphorylation and glycosylation on hydroxy and amino functions of amino acids; and, in future programs prediction of modification potential of proteins as it relates to the multifunctional nature of proteins in vivo.